PENGARUH PERPUTARAN KAS DAN PERPUTARAN PERSEDIAAN BARANG DAGANG TERHADAP LIKUIDITAS PADA CV. ANUGRAH SUKSES MANDIRI - Novela; Oktalina, Gayatria; Panjaitan, Fery (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This research was conducted from January 2024 to May 2024 and consists of 81 pages excluding appendices. The objectives of this study is to determine the influence of Cash Turnover and Inventory Turnover on Liquidity at CV. Anugrah Sukses Mandiri. The results indicate, firstly, that Cash Turnover does not have a partial effect on Liquidity, with the significance value of the Cash Turnover variable showing a t-value of 1.519, which is less than the t-table value of 2.034515, and a significance of 0.138, which is greater than 0.05. Secondly, Inventory Turnover has a partial effect on Liquidity, with the significance value of the Inventory Turnover variable showing a t-value of 21.241, which is greater than the t-table value of 2.034515, and a significance of 0.001, which is less than 0.05. Lastly, the simultaneous influence of Cash Turnover and Inventory Turnover on Liquidity shows a significant effect, with an F-value of 235.342, which is greater than the F-table value of 3.284918, and a significance of 0.001, which is less than 0.05. Liquidity when both Cash Turnover and Inventory Turnover are zero. The Cash Turnover coefficient of -0.006 indicates that each unit increase in cash turnover is associated with a 0.006 unit decrease in liquidity, assuming other factors are held constant. Although this effect is small, the negative direction suggests that higher cash turnover potentially reduces liquidity.